“Eu acho que esse papo deveria ser mais aberto”: discursos sobre autoria acadêmica em uma comunidade de estudos linguísticos - Schmidt, Ana Paula Carvalho (2016)
The authorship of scientific papers has been largely debated in many areas of knowledge. The search for prestige in the academic career and the pressure exerted by institutions and funding agencies are some of the causes of heated discussions in the academic field on authorship and themes related to it. As a result, a number of articles on this topic has been published. However, we noticed that academic authorship has been little explored in Linguistics, especially regarding the students' point of view. Therefore, based on Critical Discourse Analysis (CDA) (GEE,1999; FAIRCLOUGH, 2003), Legitimate Peripheral Participation learning theory (LAVE; WENGER, 1991; WENGER, 1998) and the perspective of academic literacies (LEA; STREET, 1998), we aim to offer an interpretation of the discourse on academic authorship, especially in order to unveil power relations as perceived by graduate students in Linguistics in a public university in southern Brazil. An ethnographic perspective (SAVILLE-TROIKE, 1989; HEATH; STREET, 2008) was adopted to generate data. The results indicate that the participants are mainly engaged in genres such as article and abstract. However, the meaning attributed to articles seems to vary across the different levels of the professional career: undergraduate students, graduate students and professors. It is also possible to observe authorship and coauthorship practices being constructed in diverse ways, which indicates a lesser or greater degree of consciousness about this question. We argue that authorship and coauthorship practices are embedded in power relations and tensions as mapped in the graduate students’ discourse. Finally, we suggest that the question of academic authorship should be more openly debated across the courses, research groups and in conferences in the area.